2017
DOI: 10.1016/j.jgeb.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimisation of xylanase production by estuarine Streptomyces sp. and its application in clarification of fruit juice

Abstract: Recently, xylanase has become an essential option for environmental friendly industrial biotechnological applications and the rising demand for its large scale production urge to take the advantage of statistical approach of optimization to investigate the interactive effects of prominent process factors involved to enhance xylanase production. In the present study, xylanase production from Streptomyces sp. strain ER1 isolated from Cochin estuarine soil; was optimised using statistical designs- Plackett-Burman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…This increases the clarity, aroma, and color of the juice (Danalache et al 2018). Xylanase from Streptomyces sp was used for the clarification of orange, mousambi, and pineapple with 20.9%, 23.6% and 27.9% clarity, respectively (Rosmine et al 2017). Immobilized xylanase obtained from Bacillus pumilus VLK-1 was used for orange (29%) and grape juice (26%) enrichment .…”
Section: Fruit Juice Clarificationmentioning
confidence: 99%
“…This increases the clarity, aroma, and color of the juice (Danalache et al 2018). Xylanase from Streptomyces sp was used for the clarification of orange, mousambi, and pineapple with 20.9%, 23.6% and 27.9% clarity, respectively (Rosmine et al 2017). Immobilized xylanase obtained from Bacillus pumilus VLK-1 was used for orange (29%) and grape juice (26%) enrichment .…”
Section: Fruit Juice Clarificationmentioning
confidence: 99%
“…Some of the most commonly agro-residues used as a cheap and renewable carbon source for xylanase production and for developing biotechnological processes of industrial interest; as wheat bran (El Shamy et al 2016), wheat husk (Kumar et al 2018), different and numerous of agricultural wastes, and different vegetable leaf industries and groundnut shell (Rosmine et al 2017;Sindhu et al 2017). A recent study also showed that wastewater from the pulp industry was reused as medium for xylanase production (de Queiroz-Fernandes et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the induction of xylanases from allochthonous bacteria growing in orange processing (by)products are limited in number, while no work on indigenous xylanolytic microbiota isolated from orange juice processing waste exists in the international literature. Streptomyces [40][41][42] and Bacillus/Geobacillus [43,44] spp. isolated from soil are common bacterial strains that have found to exhibit endo-β-1,4-xylanase activities when tested on orange processing (by)products.…”
Section: Resultsmentioning
confidence: 99%